2023
DOI: 10.1111/xen.12813
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of xenotransplantation by patients waiting for organ donation: A qualitative study

Abstract: BackgroundThe aim of this study was to determine the acceptance and barriers to xenotransplantation in patients waiting for organ transplantation.MethodsIt is qualitative and descriptive research. It was completed with 18 patients receiving treatment and waiting for organ transplantation in a dialysis center located in the inner region of Turkey between January 26, 2023 and February 3, 2023. Data were collected with an introductory information form and a semi‐structured interview form. The research data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Conversely, among 18 patients awaiting kidney donations while on dialysis in Turkey, it was observed that factors such as prejudice, fear of ridicule, religious pressure, and religious beliefs were mentioned as key considerations by the participants 21 . Likewise, within the demographic of African immigrants residing in Spain, the prevailing sentiment regarding xenotransplantation was predominantly unfavorable and influenced by a multitude of psychosocial factors 22 .…”
Section: Views Of Xenotransplantationmentioning
confidence: 99%
“…Conversely, among 18 patients awaiting kidney donations while on dialysis in Turkey, it was observed that factors such as prejudice, fear of ridicule, religious pressure, and religious beliefs were mentioned as key considerations by the participants 21 . Likewise, within the demographic of African immigrants residing in Spain, the prevailing sentiment regarding xenotransplantation was predominantly unfavorable and influenced by a multitude of psychosocial factors 22 .…”
Section: Views Of Xenotransplantationmentioning
confidence: 99%
“…For example, one study in Turkey found that “social and religious values, positive, negative and future thoughts” were a recurrent theme in participants’ views on xenotransplantation. However, more thorough, survey-based quantitative studies in Muslim countries are needed to assess people’s attitudes towards xenotransplantation [ 25 ]. That is the main objective of this study.…”
Section: Introductionmentioning
confidence: 99%